The Role Of Ict Adoption And Open Innovation In Affecting Business Resilience In F&B Msmes - Arif Rahmansyah; Keumala Hayati (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
MSMEs play a vital role not only in generating income but also in reducing unemployment, supporting regional development, and absorbing labor; however, many F&B MSMEs still face significant challenges, particularly limited innovation and low adoption of digital technology, which hinder their growth and performance. This study aims to examine the influence of ICT adoption and open innovation on business resilience using the framework of Dynamic Capabilities Theory and Open Innovation Theory. Employing a quantitative approach, data were collected from 112 F&B MSME owners in Bandar Lampung and analyzed through multiple linear regression. The results indicate that ICT adoption  (β = 0.685, p = 0.000) and open innovation (β = 0.251, p = 0.000) have positive and significant effects on business resilience, with a coefficient of determination (R2) of 0.694, indicating that the independent variables explain 69.4% of the variation in business resilience. The novelty of this research lies in the integrative testing of internal digital capabilities and external knowledge collaboration, which collectively strengthen business resilience at the local level. These findings provide empirical evidence that the integration of digital technology and collaborative innovation strategies is crucial for F&B MSMEs to overcome resource constraints and enhance competitiveness in a dynamic business environment.